Phosphorus recovery by re-dissolution from activated sludge – effects of carbon source and supplementation level revisited. Issue 1 (22nd November 2022) - Anders, Annika; Weigand, Harald; Platen, Harald
Abstract : Acetate most efficiently induced fast biological phosphorus re-dissolution from activated sludge of a full-scale WWTP, which contributes to the development and implementation of environmentally friendly phosphorus recovery strategies. Abstract : Municipal sewage sludge is a sink for wastewater-borne phosphorus (P) and a source for P recovery. Many wastewater treatment plants (WWTPs) employ the enhanced biological P removal (EBPR) which relies on the ability of polyphosphate accumulating organisms (PAOs) to store P in the biomass. Inversion of EBPR may provide a tool for on-site P recovery from activated sludge (AS). Key features of anaerobic P release and the metabolism of acclimated PAOs are well known from laboratory experiments. However, uncertainty persists regarding the behavior of non-acclimated sludge which hampers the practical implementation of P recovery. In this light, we revisited the effects of volatile fatty acid supplementation (formate, acetate, propionate, and butyrate) on the anaerobic P re-dissolution from non-acclimated AS of a full-scale WWTP. All supplementations induced P re-dissolution but the highest re-dissolution was observed with acetate (1.54–1.68 mmol P L −1 ) with a Pyield /VFAconsumed ratio of 0.45. For AS with 6.3 gTSS L −1, a supplementation level of 200 mg L −1 acetate was most efficient. Recovery amounted to 21–24% of total P within 300 min. Surprisingly, P re-dissolution continued even after acetate had been fully consumed. From the energetic viewpoint, this seems contradictory. Therefore, we integrated the process stoichiometry with known metabolic pathways accounting for the main electron, energy, carbon and P flows for the acetate-induced P re-dissolution. Results show that induction of anaerobiosis in AS from the EBPR process is, indeed, a viable technical option for P recovery. Yet, efficiency needs to be improved since P re-dissolution was either limited by acetate uptake capacity or by available polyphosphate.